Can we combine 3D data obtained with a MicroScribe digitising arm and photogrammetry to address bioarchaeological research questions?. (December 2022) - Collard, Mark; Dobney, Keith; Plomp, Kimberly A.
Highlights: Is it valid to combine 3D data obtained with a digitising arm and photogrammetry? To address this question, we simulated a comparative bioarchaeological analysis. Photogrammetry revealed facial differences not captured by the digitising arm. Also, the two methods did not consistently capture the same facial shapes. Bioarchaeologists should be cautious about combining these types of 3D data. Abstract: Virtual methods for studying human remains are becoming increasingly popular in bioarchaeology, and the rate of technological innovation in the last few years has been such that we now have multiple options to choose from when collecting data. This raises the question of whether datasets generated with different methods are transposable. In the study reported here, we investigated whether it is valid to combine 3D data obtained with a MicroScribe digitising arm and 3D data collected via photogrammetry. We did so by simulating a population-based analysis similar to those commonly undertaken in bioarchaeology. Our sample comprised 19 crania from two ethnic groups, Ancient Egyptians and Guanches, and the landmarks we employed pertained to facial shape. The analyses yielded several findings. First, we found that photogrammetry was significantly more precise than the MicroScribe digitising arm. Second, the photogrammetry-based method revealed the existence of facial shape differences between the two ethnic groups that were not captured by the MicroScribe-based method. Third, we found that the two methods did not consistently capture the same facial shapes—they did for one of the ethnic groups but not for the other. Fourth, the analyses indicated that using the two methods can result in ethnic group-level differences in facial shape when they are applied to individuals from a single ethnic group. Lastly, the two methods of data collection yielded different patterns of variation in facial shape. Together, these findings suggest that combining 3D landmark coordinates collected with a MicroScribe and those obtained via photogrammetry may introduce considerable error into an analysis, and, consequently, bioarchaeologists should be cautious about doing so.